2013
DOI: 10.1111/gcb.12269
|View full text |Cite
|
Sign up to set email alerts
|

Dampening effects of long‐term experimental drought on growth and mortality rates of a Holm oak forest

Abstract: Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13 years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(207 citation statements)
references
References 65 publications
15
192
0
Order By: Relevance
“…In ecosystems facing severe spells of drought, plant assimilation is strictly dependent on water availability [42][43][44][45], whose duration controls the length of the growing season [46][47][48]. In this study, photosynthesis showed a strong seasonal variation, as confirmed by the significant correlation of Anet Table A3. SIR and total El-FAME were both significantly mostly correlated with SR h , with the exception of carbohydrates and amino acids, and fungi and protozoa respectively (Table 4).…”
Section: Discussionsupporting
confidence: 66%
“…In ecosystems facing severe spells of drought, plant assimilation is strictly dependent on water availability [42][43][44][45], whose duration controls the length of the growing season [46][47][48]. In this study, photosynthesis showed a strong seasonal variation, as confirmed by the significant correlation of Anet Table A3. SIR and total El-FAME were both significantly mostly correlated with SR h , with the exception of carbohydrates and amino acids, and fungi and protozoa respectively (Table 4).…”
Section: Discussionsupporting
confidence: 66%
“…However, fewer studies have attempted to identify the underlying functional problem in "weak" individuals. Most of the studies dealing with the decline of holm oak at individual tree level have focused mainly on characterizing the effects or symptoms of decay in the aerial part of the stools, both at leaf and xylem level (Tognetti et al, 1998;Camarero et al, 2004;Corcuera et al, 2004), sometimes through water exclusion experiments (Limousin et al, 2009;Barbeta et al, 2013;Pérez-Ramos et al, 2013). However, because holm oak is a species with a strong resprouting capacity and as most of the stools have been managed in a coppice system over a long period of time, it would seem reasonable to assume that the cause of decay of some stools may be at least partially explained by factors relating to the root system .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 60 to 80 % of the French metropolitan territory may experience a Mediterranean type climate by the end of the twenty-first century (Roman-Amat 2007). The acclimation of existing forest stands to increasing drought relies on different physiological adjustments, among which leaf area reduction seems of particular importance over the long term (Martin-StPaul et al 2013), and may be related to changes in stem density (Barbeta et al 2013). Thinning operation, which modulates stem density and stand vertical structure, can thus accelerate this stand acclimation and has been reported to improve tree resistance to drought stress (Misson et al 2003) and post-drought resilience (Martín-Benito et al 2008;Sohn et al 2013).…”
mentioning
confidence: 99%